Content of Fatty Acids and Phenolics in Coratina Olive Oil from Tunisia: Influence of Irrigation and Ripening. Issue 3 (March 2015) - Dabbou, Samia; Dabbou, Sihem; Chehab, Hechmi; Taticchi, Agnese; Servili, Maurizio; Hammami, Mohamed
Abstract The quality indices and chemical composition of Coratina olive oil produced in the northern region of Tunisia were evaluated, to determine the effect of three different irrigation regimes of the trees on the olive oils. The olives were sampled at two different stages of maturity, the oils were extracted, and standard methods were used to analyze the composition and quality of the oils. The fatty‐acid contents and quality parameters were only slightly affected by the irrigation regime. The contents of palmitic, oleic, and linoleic acids were above 12, 72, and 8%, respectively, for the second harvest, regardless of the irrigation level of the olive trees. Parameters such as the α‐tocopherol content and the phenolic profile were found to be significantly affected by the harvesting time; however, inconsistent changes were observed for the irrigation regimes, especially for the oil of the second harvest. It was shown that the irrigation conditions of the olive trees as well as the harvesting time of the fruits gave rise to a diverse range of olive oils in Tunisia.